Does banks' systemic importance affect their capital structure and balance sheet adjustment processes? - Yassine Bakkar; Olivier De Jonghe; Amine Tarazi (National Bank of Belgium, 2019)
Frictions prevent banks to immediately adjust their capital ratio towards their desired and/or imposed level. This paper analyzes (i) whether or not these frictions are larger for regulatory capital ratios vis-à-vis a plain leverage ratio; (ii) which adjustment channels banks use to adjust their capital ratio; and (iii) how the speed of adjustment and adjustment channels differ between large, systemic and complex banks versus small banks. Our results, obtained using a sample of listed banks across OECD countries for the 2001-2012 period, bear critical policy implications for the implementation of new (systemic risk-based) capital requirements and their impact on banks' balance sheets, specifically lending, and hence the real economy.
Keywords: G20; G21; G28; 330; capital structure; speed of adjustment; systemic risk; systemic size; bank regulation; lending; balance sheet composition